Evaluation of zootechnical and reproductive parameters of wild populations of Sarotherodon melanotheron Rüppell, 1852 of Southern Benin raised in captivity. - AMOUSSOU, T. Olivier; Toguyeni, Aboubacar; IMOROU TOKO, Ibrahim; CHIKOU, ANTOINE; BRAVO, Mevis; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2017)
Tilapia Sarotherodon melanotheron is naturally adapted to both fresh and brackish environments. In order to improve its farming potential, this study evaluated the growth, survival and reproductive parameters of individuals from three lakes of southern Benin according to their sex and age at experimental fishing. During fry rearing and breeding, fish were fed with commercial feed granulated. The chlorophyll a concentration and the abundance of plankton were determined by molecular absorption spectrometry and under a light microscope respectively. Physico-chemical parameters were within acceptable limits for good survival and growth of S. melanotheron. Together with chlorophyll a, three phytoplankton species and five zooplankton species were also available in the rearing tanks. At the end of the experiment (90 days post nursery), most of the growth parameters did not vary significantly according to the waterway of origin and the sex. However, the a ge at experimental fishing influenced significantly most of the growth parameters. The individuals from Lake Nokoué and Lake Toho were characterized by higher body weight, total length, standard length, weight gain, average weight gain, daily weight gain, nutritive quotient, survival rate, net biomass, biomass per square meter while Grand-Popo Lagoon individuals were characterized by higher ccondition factor and a weak ponderal and linear specific growth rates. Overall, reproductive parameters were higher in females than males. The majority of males were with empty testicles, while females with ova were expelled by manual pressure. S. melanotheron individuals from the considered lakes can be recommended for selective breeding program in fresh and brackish waters.
Keywords: Benin; Sarotherodon melanotheron; aquaculture; captivity; growth; reproductive parameters